Active Vibration Control of Railway Vehicle Car Body by Secondary Suspension Actuators and Piezoelectric Actuators - Hui Cao; Gangjun Li; Ning Liang (IEEE Access, 2022)
Active vibration suppression of high-speed electric multiple unit (EMU) car bodies was studied by the combined use of secondary suspension actuators and piezoelectric actuators. A vertical dynamics model was established considering secondary suspension actuators and piezoelectric actuators. The positions of the piezoelectric actuators and sensors were optimized using $H_{2} $ and $H_{∞ } $ norms. The feedback controller was designed using a robust optimal control method. The effects of the vibration devices and active control methods on the vehicle dynamic performance were simulated using MATLAB. The dynamic performance differences among the passive suspension vehicle, secondary vertical actuator installation vehicle, and active vibration control vehicle were compared and analyzed. The results show that the piezoelectric actuators and piezoelectric sensors were arranged at distances of 7.15, 12.25, and 17.35 meters from the left end of the car body, and the normalized $H_{2} $ and $H_{∞ } $ norms of the first and second order elastic modes of the car body were the largest, which can be used as piezoelectric actuators and sensor placement positions. Secondary suspension actuators can reduce rigid car body vibrations, and piezoelectric actuators can reduce elastic vibration. The higher the speed, the better is the acceleration suspension effect. When the vehicle speeds were 200 km $· \text{h}^{-1}$ and 350 km $· \text{h}^{-1}$ , the vehicle vibration acceleration decreased by 10% and 18%, respectively. Compared with the passive suspension system, the active vibration suspension system with a robust controller can reduce the rigid and elastic vibrations of the vehicle and improve ride comfort.